The Shades of Grey: Datenherrshaft in Data-driven Gamification - Sami Hyrynsalmi; Kai Kimppa; Jani Koskinen; Jouni Smed; Sonja Hyrynsalmi (My University, 2025)
Data-driven gamification refers to the use of data collection and data science methods together with gamification practices in order to improve the selected aspects of a service or a product. As new innovations cause new ethical questions, this study surveys possible ethical problems of data-driven gamification. Precisely, we focus on the ethical question of using data collected from a user to modify behaviour of the user. Instead of a clearly bright or dark side of the force, we focus on the ethically grey area where intentions might be ethically justified while the results are not. To discuss this dilemma, we borrow the concept of ‘Datenherrschaft’—mastery over information—and present a philosophical inquiry of five cases: Leisure, Governmental, Healthcare, Educational and Workplace solutions. As a result, this study shows that there are clearly ethical issues, different shades of grey, related to the data-driven gamification and future work is needed in order assess, analyze and answer the presented problems.
Proceedings of the First International Workshop on Data-Driven Gamification Design